THE EFFECT OF DISCOVERY LEARNING AND THINK PAIR SHARED LEARNING MODELS ON STUDENTS’ ACHIEVEMENT IN SCIENCE AT GRADE IV ELEMENTARY SCHOOL (IN THE VIEW OF LEARNING MOTIVATION) - Iqbal; Desi Riskasusanti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study was a quasi-experimental research. The population of this study were all grade IV students of SD Negeri 16 Kota Banda Aceh. The samples in this study were students at grade IV A and IV B, who were chosen by using total sampling techniques. The instrument in this study was a science learning achievement test and a motivation questionnaire. Then, the data were analyzed by using two-way ANOVA at a significant level of Alpha 0.05. The results of this study indicated that: (1) Discovery Learning and Think Pair Share learning models gave significant effects on the students’ achievement in science learning. This was demonstrated by the average score of learning achievement for DL class of 81.87 and the average score of learning achievement for TPS class of 74.27, with a sig. value 0,000; (2) there was an effect of learning motivation on the students’ science learning achievement which was seen from the average score of the learning achievement of highly motivated students for as much as 81.87. Meanwhile, the average score of learning achievement of students with low motivation was 74.27, with a sig. value of 0,000; (3) there was no interaction between Discovery Learning and Think Pair Shared learning models in terms of students’ learning motivation towards science learning achievement at grade IV, with a sig. value of 0.086.